Dipeptidyl peptidase‐4 inhibitor might exacerbate Graves' disease: A multicenter observational case–control study. Issue 11 (16th June 2021) - Sekizaki, Tomonori; Kameda, Hiraku; Nomoto, Hiroshi; Cho, Kyu Yong; Nakamura, Akinobu; Takahashi, Kiyohiko; Miyoshi, Arina; Wada, Norio; Takeuchi, Jun; Nagai, So; Miyoshi, Hideaki; Atsumi, Tatsuya
Abstract: Dipeptidyl peptidase‐4 (DPP‐4), namely CD26, is expressed on the surface of immune cells, suggesting that inhibition of DPP‐4 might affect the immune system. The current multicenter observational case–control study was carried out to investigate the effects of DPP‐4 inhibitor (DPP‐4i) administration on Graves' disease (GD) activity. This study comprised patients with GD and type 2 diabetes, who were administered an oral hypoglycemic agent including DPP‐4i. Exacerbation of GD was defined as an increase of antithyroid drug dose by 6 months after oral hypoglycemic agent administration. A total of 80 patients were enrolled and divided into an exacerbation group or a non‐exacerbation group. The frequency of DPP‐4i administration was significantly higher in the exacerbation group (88%) than that in the non‐exacerbation group (31%). In multivariate logistic regression analysis, there was a significant association between DPP‐4i administration and GD exacerbation (odds ratio 7.39). The current study suggests that DPP‐4i administration is associated with GD exacerbation. Abstract : The frequency of dipeptidyl peptidase‐4 inhibitor administration was significantly higher in the Graves' disease exacerbation group than that in the non‐exacerbation group. Multivariate logistic regression analysis also showed a significant association between dipeptidyl peptidase‐4 inhibitor administration and Graves' disease exacerbation. Our study has proven the potential association of dipeptidyl peptidase‐4 inhibitor administration with Graves' disease exacerbation.